How livelihood strategies affect spatial differentiation of relative poverty of rural households: evidence of Chinese rural areas based on the GWR model - Huo, Zenghui; Yang, Yuhui; Yang, Ying; Zhou, Jing; Zhang, Mei (Frontiers in Sustainable Food Systems, 2025)
IntroductionGiven China’s vast geographic diversity and significant regional development disparities, it is crucial to explore whether the livelihood strategies of rural households in different regions influence relative poverty outcomes spatially.MethodsThis study utilizes survey data from 892 rural households to investigate the agglomeration of relative poverty among rural households, employing both global and local Moran’s I indices. Additionally, a geographically weighted regression (GWR) model is used to analyze the spatial differentiation of the impact of livelihood strategies on rural households’ relative poverty.Results and discussionA positive spatial autocorrelation exists between relative poverty and livelihood strategy variables, indicating an overall trend of high-value clustering. The local Moran’s I index shows significant spatial clustering of relative poverty among rural populations, with distinct characteristics across regions. In economically developed areas, relative poverty among rural populations exhibits a “low-low” agglomeration pattern, whereas in economically underdeveloped areas, it manifests as a “high-high” agglomeration. The GWR results reveal that the impact of various livelihood strategies differs significantly. The business-oriented livelihood strategy has a substantial inhibitory effect on relative poverty, whereas the employment-based strategy tends to exacerbate it. In contrast, the agriculture-based livelihood strategy exhibits a dual effect. The kernel density of regression coefficients illustrates spatial differentiation in the impacts of different livelihood strategies. In rural areas closer to markets, business livelihood strategies can reduce relative poverty among rural populations. Additionally, in rural areas close to economically developed cities, income from employment is more effective in helping families overcome poverty. Engaging in specialty agricultural production can also help diminish relative poverty; however, rural households in remote mountainous areas, who lack access to specialty agriculture, may find that traditional agricultural practices further exacerbate their relative poverty.